Stock Risk as a Moderator in the ESG-Return Relationship: Evidence from the Indonesian Capital Market - ZULI, WAHFI; Usman, Berto; Nikmah, Nikmah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study analyses the influence of Environmental, Social, and Governance (ESG) performance on stock returns, with stock risk—measured by volatility—introduced as a moderating factor. Methodology: Using a sample of 33 companies listed in the IDX ESG Leaders and SRI-KEHATI indices between 2021 and 2023, ESG data were derived from the CESGS Universitas Airlangga dataset, returns were calculated through capital gains, and volatility was estimated from standard deviations of monthly returns. Panel regression with a Fixed Effect Model was employed. Results: Findings demonstrate that ESG performance negatively affects stock returns, and this negative impact intensifies in conditions of higher volatility. Findings: These results suggest that investors in Indonesia prioritise short-term financial risk over sustainability credentials, which weakens the signalling role of ESG. Novelty: This research introduces volatility as a moderator in the ESG–return nexus and provides evidence from ESG-specific indices in Indonesia (IDX ESG Leaders and SRI-KEHATI). Originality: The research highlights the Indonesian market context, showing that ESG has not yet emerged as a positive driver of stock returns. Conclusion: The study highlights that ESG in emerging markets requires stronger regulatory support and enhanced disclosure to translate sustainability practices into financial value.. Type of Paper: Research article.